Negotiating Value and Faith: The Practice of Scrap-for-Goods Exchange in Sukowono, Indonesia, through the Lens of Fiqh Muamalah - Imania, Dela Jannatul; Mohammad Firmansyah (Fakultas Syariah UIN Prof. K.H. Saifuddin Zuhri, 2025)
The practice of exchanging scrap materials for new goods in Sukowono District represents a form of community economic activity that has become a local habit and carries social and economic benefits, particularly among housewives. This system is preferred because it is more practical and provides direct benefits for meeting household needs. This study aims to describe the practice of scrap-for-goods exchange conducted by the community and to analyze it from the perspective of Islamic economic law (fiqh muamalah), particularly in terms of justice, mutual consent (taradhi), and transparency. This research employs a socio-legal approach with qualitative methods through observation and interviews with scrap traders and participants in Sukowono District, Jember Regency. The findings show that the exchange practice is carried out through two systems: the weighing system and the estimation system. The weighing system is considered more in line with Islamic principles because it is clear, measurable, and transparent. Meanwhile, the estimation system contains elements of gharar (uncertainty) since the value of goods is determined by approximation without exact measurement. Overall, this exchange practice is deemed valid under fiqh muamalah as it fulfills the elements of mutual consent and clear transaction objects; however, price transparency needs to be improved to better reflect the principles of justice and honesty in Islamic transactions.